The typically developing paediatric foot: how flat should it be? A systematic review - Hayley Uden; Rolf Scharfbillig; Ryan Causby (Journal of Foot and Ankle Research, 2017)
Abstract Background All typically developing children are born with flexible flat feet, progressively developing a medial longitudinal arch during the first decade of their lives. Whilst the child’s foot is expected to be flat, there is currently no consensus as to how flat this foot should be. Furthermore, whilst feet are observed to decrease in flatness with increasing age, it is not known how flat they should be at each age increment. The objective of this systematic review is to define the postural characteristics of the ‘typically’ developing paediatric foot. Methods The PRISMA protocol was applied to compare all data currently published describing the typical development of the paediatric foot. The Epidemiological Appraisal Instrument (EAI) was used to assess the risk of bias of the included studies. Results Thirty four epidemiological papers pertaining to the development of the paediatric foot were graphically compared. Sixteen different foot posture assessments were identified of which footprint based measures were the most reported outcome. Conclusion Firstly, the use of the term normal in relation to foot posture is misleading in the categorisation of the paediatric foot, as indeed a flat foot posture is a normal finding at specific ages. Secondly, the foot posture of the developing child is indeed age dependent and has been shown to change over time. Thirdly, no firm conclusion could be reached as to which age the foot posture of children ceases to develop further, as no two foot measures are comparable, therefore future research needs to consider the development of consensus recommendations as to the measurement of the paediatric foot, using valid and reliable assessment tools.